PHYTOCHEMICAL SCREENING AND ANTIAMEBIC STUDIES OF TAMARINDUS INDICA OF LEAVES EXTRACT - H MEHDI, MANSOUR ABDULNABI; YS ALARABI, FADEL; FAROOQUI, MAZAHAR; PRADHAN, VIDYA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study deals with preliminary phytochemical screening of Tamarindus indica extracts and investigates its antiamebic effect against Entamoeba histolytica in vitro. Methods: E. histolytica was isolated from stools of patients with amebic dysentery and cultivated in lock-egg medium. The leaves extract was added to check its antiamebic activity. Results: The phytochemical screening shows that T. indica contains alkaloids, flavonoids, phenol, and tannins. T. indica extracts (aqueous and ethanolic) were added to culture media E. histolytica. It was observed that E. histolytica count reduced to zero after 72 h and 96 h when 15 mg/ml of aqueous and ethanolic extracts were added, respectively. It is also revealed that there is no cytotoxicity against erythrocytes even when high concentration of plant leaves extract is used. Conclusion: The in vitro sensitivity of T. indica leaves extract against the E. histolytica is established.